Effectiveness of clean intermittent self catheterization in patients with recurrent urethral stricture post visual internal urethrotomy - Ullah, Naqib; Nawaz, Jamshid; Shoaib, Muhammad; Khan, Asif; Din, Nizam ud; Fareed, Tauheed (Journal of Rawalpindi Medical College, 2023)
OBJECTIVE : Objective of the study is to determine the effectiveness of CISC in management of recurrent urethral strictures after visual internal urethrotomy. METHODOLOGY : This study performed in department of urology Saidu teaching hospital Swat from June 2016 to July 2019 on 215 patients who were diagnosed as having urethral stricture disease. Patients were counseled for CISC after removal of catheter 2 times a day for 8 weeks and at 8th week cystourethroscopy performed along with detail evaluation of symptoms of urethral stricture to know recurrence of stricture. RESULTS: 81.39% patients have no urethral stricture on cystourethroscopy and symptomatic evaluation at 8th week post visual internal urethrotomy while 18.60% patients have recurrent urethral stricture . Length of urethral stricture is the most important prognostic factor, stricture of less than 1 cm has success rate of 62.39% while stricture of more than one cm length has success rate of 20% as shown in table IV. CONCLUSION: In this study it has been confirmed that CISC is safe ,cost effective procedure and most of the patients can do it in home with out any complications.